10.47313 Feminism in Women Talking Movie: A Main Character Analysis - Arum, Shalma Lestari; S., Nurhayati; Fadilah, Fadilah (Pujangga, 2025)
As a form of literary work, the movie can be a medium to disseminate information and issues concerning society. One of the issues often raised in a movie story is feminism. Feminism itself is a movement that seeks equality between men and women. This research takes the movie Women Talking as its object. This study aims to analyze feminism portrayed by the female main character in the Women Talking movie, mainly focusing on the types, factors, and moral values. This research uses a qualitative descriptive method. The theories used in this research are Tong's feminism theory for the types of feminism. The data collection techniques used were observation and documentation of Women Talking movies related to feminism by recording the indicators of feminism in the movie scenes, including duration, images, and dialogue. The results of this study show that the driving factor for the emergence of feminism by the main character in this movie is ending domestic violence and abuse. As for the type of feminism, it was found that the main character of this movie depicts liberal feminism and radical feminism.